2017
DOI: 10.13075/ijomeh.1896.00919
|View full text |Cite
|
Sign up to set email alerts
|

Occupational diseases in the automotive industry in Czechia – Geographic and medical context

Abstract: Objectives:The automotive industry represents the most important industrial sector in Czechia. The objective of this study has been to analyze the occurrence of occupational diseases (OD) in the automotive industry during the period from 2001 till 2014. Material and Methods: Data on OD cases was retrieved from the National Registry of OD. Further, we conducted a survey in automotive companies with focus on occupational health services and positions of the companies in global production networks (GPNs). An anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
9
2
Order By: Relevance
“…These ndings are consistent with those reported by other authors, who reached similar conclusions. [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings are consistent with those reported by other authors, who reached similar conclusions. [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we extended our previous research covering the period of 2001-2014 and involving the Czech Republic only (14). Here we analyzed the situation in the years 2001-2017 both in Czechia and Slovakia.…”
Section: Datamentioning
confidence: 93%
“…First, the data from the Czech National Registry of Occupational Diseases and from the database of the Slovak National Health Information Centre was obtained. OD cases which occurred in the economic activity under Division 29 of the NACE classification (manufacture of motor vehicles) were retrieved and divided according to the identification number of the enterprises where the diseases originated (13,14). The other classification criterion was the size of the companies (number of employees) in terms of EU 2003/361/EC methodology.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…authors who found an OR of 1.4 [18]. Speci cally, the largest OR was found when the hand tool put pressure on the palm, followed by when the mechanical pressure was exerted on the ngers [19][20]. In any case, the use of hand tools deserves further study in order to determine its impact more precisely.…”
mentioning
confidence: 98%